2009
DOI: 10.1111/j.1462-2920.2009.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Limits of life in hostile environments: no barriers to biosphere function?

Abstract: SummaryEnvironments that are hostile to life are characterized by reduced microbial activity which results in poor soil-and plant-health, low biomass and biodiversity, and feeble ecosystem development. Whereas the functional biosphere may primarily be constrained by water activity (a w) the mechanism(s) by which this occurs have not been fully elucidated. Remarkably we found that, for diverse species of xerophilic fungi at a w values of Յ 0.72, water activity per se did not limit cellular function. We provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
258
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(269 citation statements)
references
References 78 publications
9
258
0
2
Order By: Relevance
“…In accordance with our hypothesis (but nevertheless, to our surprise), cells preferentially synthesized and accumulated a chaotropic-compatible solute, glycerol ( Fig. 3B) (13). It is energy expensive to both synthesize compatible solutes de novo and to retain them in the cell, and indeed, the cost imposed to the cellular system is known to determine the limits of microbial growth windows under stressful conditions (e.g., low water activity or ethanol stress) (21,22).…”
Section: Fungi Preferentially Accumulate Chaotropic Metabolites At Lowsupporting
confidence: 71%
See 2 more Smart Citations
“…In accordance with our hypothesis (but nevertheless, to our surprise), cells preferentially synthesized and accumulated a chaotropic-compatible solute, glycerol ( Fig. 3B) (13). It is energy expensive to both synthesize compatible solutes de novo and to retain them in the cell, and indeed, the cost imposed to the cellular system is known to determine the limits of microbial growth windows under stressful conditions (e.g., low water activity or ethanol stress) (21,22).…”
Section: Fungi Preferentially Accumulate Chaotropic Metabolites At Lowsupporting
confidence: 71%
“…2 R-T). Although the mechanisms by which diverse solutes exert chaotropic activity are not yet wellunderstood, the net effects of ionic, nonionic, and hydrophobic chaotropes (9, 10, 18) may be indistinguishable to the cell (13). † Our data show that M. frigida growth was rapid at the highest incubation temperature (+1.7°C), regardless of medium type, but that growth rates were greatly enhanced on all chaotropesupplemented media relative to that on the kosmotropic medium at subzero temperatures ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grant (2004) revealed that high-sugar foods (with low aw) are mainly dominated by xerophilic fungi and osmophilic yeasts. However, the presence of halotolerant bacteria in these foods was often reported, although the osmotic stress imposed by cations (salts) and uncharged organic solutes (like sucrose) is not the same (Williams and Hallsworth 2009). Recently, a halotolerant bacterium Tetragenococcus halophilus was found to be dominant (>99 %) in a high-sugar Bthick juice^ (Justé et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is expected that one would find many halotolerant bacteria in Btana samples, such as: Corynebacterium, Acinetobacter, Acidovorax, Propionibacterium, Staphylococcus and Peptostreptococcus (De Vos et al 2009). Moreover, osmotolerance is linked with the availability of osmoprotectants in the surrounding medium to help bacteria to maintain the internal homeostasis (Williams and Hallsworth 2009). Interestingly, it was reported that dates are very rich in proline (12-369 mg/100 g), choline (6.30-9.90 mg/100 g), betaine (0.4 mg/100 g), and also contain a high level of potassium (703-1130 mg/100 g) (Favier et al 1993;Al-Shahib and Marshall 2002;El-Sohaimy and Hafez 2010;Kchaou et al 2013).…”
Section: Discussionmentioning
confidence: 99%